RESEARCH ON HEIDELTIME WITH VIETNAMESE LANGUAGE PROCESSING AND EXPERIMENTAL APPLICATION DEVELOPMENT AND EVALUATION - Dien Thi Hong Ha (Tạp chí Khoa học)
This paper presents software development for searching and extracting temporal information from text to help users access and understand content from electronic documents stored on organizational computer systems and websites using the HeidelTime tool. HeidelTime is a natural language processing tool customized to analyze temporal elements in Vietnamese contexts. The research methodology includes the following key steps: Surveying systems and user needs for time-based text search; analyzing and selecting natural language processing techniques, where HeidelTime is applied to identify and extract temporal information from Vietnamese text. The research results demonstrate that the time-based search software achieves high accuracy when deployed on the organization's document management system. It effectively supports time-based information retrieval and extraction, meeting users' practical needs. This study highlights the potential application of natural language processing technology in Vietnamese document management, contributing to improved storage and search efficiency within organizational information systems.